Testing the parent-child communication program: Its effectiveness on developing children’s social competences - Agus Mulyanto; Alifah Indalika Mulyadi Razak (REID (Research and Evaluation in Education), 2019)
Social competence has a central role in the development of early childhood. One of the central roles of children's social competence is its influence on children's academic social abilities, such as the ability to (1) receive learning information, (2) follow the school’s rules, and (3) face increasingly complex academic challenges along with increasing school levels. This study aims to test the model of parent-child communication (PCC) in developing children’s social competence. The exclusive communication model was tested to 250 children aged 4-6 years in West Java Province,  which is divided into five research zones, West Java Zone 1 to 5. This study used an experimental design pre-test and post-test to determine the effectiveness of the parent-child communication program that was tested through observation and interview techniques consisting of 68 items of social competence. The results show that the PCC Program can effectively be applied by the collaboration of parents between fathers and mothers to optimize children's social competencies. The PCC program, which was not attended by both parents, would not be effective, for example, as happened in the West Java Zone 1, indicating the ineffectiveness of the PCC program because of the characteristics of parental activities that both work and do not have time to communicate with children. While in the other four West Java Zones PCC can be effective, because working parents want to take the time to interact and communicate actively with their children.